QUALITY IMPROVEMENT OF WATER USING ELECTROCOAGULATION AND CARBON FILTER METHODS - Masthura Masthura; Ety Jumiati (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2017)
Study on the effect of comparison and improvement of water quality using electrocoagulation and carbon filter methods has been conducted. This study aims to find out a safe method to be an alternative in producing clean water up to drinking water that can be used to meet daily needs in accordance with clean water and drinking water standards. The parameters tested include physical parameters (temperature, TDS, turbidity, color, odor, and taste), chemical parameters (pH, iron (Fe), and aluminum (Al)), and microbiological parameters (E. coli and Coliform Bacteria). The test results show that water purification using activated carbon is much better than water test result by electrocoagulation method. This is reflected in physical and chemical parameters that have met the clean water standard (Permenkes RI No. 416/1990) and drinking water standard (No. 492/MENKES/PER/IV/2010). As for microbiological parameters are still not meet the clean and drinking water standards.Keywords: Activated carbon, electrocoagulation, and filters.